ASSESSMENT OF THE PROFILE OF CONSUMERS OF STINGLESS-BEE PRODUCTS IN COARI, AMAZONAS, BRAZIL - Silva Júnior, Augusto Teixeira da; Silva, Shamila Magalhães da; Carvalho-Zilse, Gislene Almeida; Cazarin, Cinthia Baú Betim; Yamaguchi, Klenicy Kazumy de Lima; Rebelo, Kemilla Sarmento (Interfaces Científicas - Saúde e Ambiente, 2026)
This study aimed to outline the profile of consumers of stingless-bee products in the municipality of Coari, Amazonas. A cross-sectional exploratory study with a quantitative-descriptive approach was conducted. A semi-structured virtual questionnaire was applied, which was disseminated through social media. A total of 113 individuals participated in this study, with the majority (54.0%) being females with a mean age of 30.4±8.8 years. Of the participants, 98.9% reported purchasing honey, 83.1% preferred to consume stingless bee honey, and 40.4% preferred to buy it at fairs/markets. However, although this preference exists, only 60.7% of the individuals declared that they could differentiate stingless bee honey from honey produced by bees with stingers. Regarding honey consumption, 5.6% of the interviewed consumers reported consuming it daily, and the main reason for buying honey is for medicinal use (64.2%). The quality of honey (85.4%) is the predominant factor influencing the choice of stingless bee products. This study provides unprecedented and essential information about the profile and expectations of buyers/consumers of stingless-bee products in Coari, Amazonas, Brazil. It serves as an important database for establishing marketing strategies that can contribute to the growth and development of meliponiculture, the protection of the stingless bee, and the local economy.